PL03.3.A Development and characterization of CD317-specific CAR T cells as an innovative immunotherapeutic strategy against glioblastoma. (9th September 2021) - Hänsch, L; Peipp, M; Myburgh, R; Silginer, M; Weiss, T; Gramatzki, D; Vasella, F; Manz, M; Weller, M; Roth, P
Abstract: BACKGROUND: Due to the limited success of existing therapies for gliomas, innovative therapeutic options are urgently needed. Chimeric antigen receptor (CAR) T cell therapy has been successful in patients with hematological malignancies. However, using this treatment against solid tumors such as glioblastomas is more challenging. Here, we generated CAR T cells targeting the transmembrane protein CD317 (BST-2, HM1.24) which is overexpressed in glioma cells and may therefore serve as a novel target antigen for CAR T cell-based immunotherapy. MATERIAL AND METHODS: CAR T cells targeting CD317 were generated by lentiviral transduction of human T cells from healthy donors. The anti-glioma activity of CD317-CAR T cells was determined in lysis assays using different glioma target cell lines with varying CD317 expression levels. The efficiency of CD317-CAR T cells to control tumor growth in vivo was evaluated in clinically relevant orthotopic xenograft glioma mouse models. RESULTS: We created a second-generation CAR construct targeting CD317 and observed strong anti-glioma activity of CD317-CAR T cells in vitro. Glioma cells with a CRISPR/Cas9-mediated CD317 knockout were resistant to CD317-specific CAR T cells, demonstrating their target antigen-specificity. Since CD317 is also expressed by T cells, transduction with a CD317-directed CAR resulted in fratricide of the transduced T cells. Silencing of CD317 in CAR T cells by integrating a specific shRNA into the CAR vector significantly increased the viability, proliferation and cytotoxic function of the CAR T cells. Importantly, intratumoral treatment with CD317-CAR T cells prolonged the survival and cured a significant fraction of glioma-bearing nude mice. CONCLUSION: We demonstrate strong CD317-specific anti-tumor activity of CD317-CAR T cells against various glioma cell lines in vitro and in xenograft glioma models in vivo. These data lay a scientific basis for the subsequent evaluation of this therapeutic strategy in clinical neuro-oncology.